Impact of information activities on people’s attitudes towards dam reservoir construction - Połomski, Maksymilian (Bulletin of Geography. Socio-economic Series, 2026)
The paper aims to identify the most significant aspects that foster people’s negative attitudes towards the construction of new dam reservoirs and to estimate the impact of outreach activities on this issue. Online surveys were conducted; the respondents selected a set of questions preceded by a graphical information leaflet, or a set with questions only. The latter included three scenarios in which the respondent was asked to identify themselves as a resident of (1) a large city, (2) a small town or (3) a village. In the group of individuals who had not received the information leaflet, 16.78%, 17.69% and 63.27% spoke negatively about scenarios 1, 2 and 3, respectively. The figures for the second group were 14.08%, 14.66% and 55.17%. For scenario 3, there was also a statistically significant decrease in negative responses for those had previously learned more about reservoir construction.